Nurturing Talent â€“ To Create a Sustainable Advantage - Chowdhary, Shraddha (Mediterranean Journal of Social Sciences, 2012)
â€œIf you have got it, keep itâ€, is the focus of all Employers in terms of its talented workforce. One of the most important strengthsof an organization lies in the quality of the workforce it has and how well itâ€™s being managed. Apart from making a right decision inchoosing the right person for the right job, the continuing presence of these capable persons in the Organization is as much necessary.Acquiring the right talent can be a tough job and retaining them can at times be tougher. Itâ€™s for this purpose that the concept of Talentmanagement has been gaining importance over the years. How the HR function has evolved over the years, what is the process of talentmanagement, what are the challenges facing talent management and how various strategies can be put into use to overcome thesechallenges have been analyzed here. â€œPeopleâ€ being considered the most important resource to an organization is one of the mostimportant factors which helps the organization have a sustainable competitive advantage over its competitors, hence the study of Talentmanagement as a process is imperative. This paper tries to identify the need to manage talent in organizations and lists certainstrategies that can create a sustainable competitive advantage by nurturing talent.